Barley beta‐glucan promotes MnSOD expression and enhances angiogenesis under oxidative microenvironment. Issue 1 (11th November 2014) - Agostini, Silvia; Chiavacci, Elena; Matteucci, Marco; Torelli, Michele; Pitto, Letizia; Lionetti, Vincenzo
Abstract Manganese superoxide dismutase (MnSOD), a foremost antioxidant enzyme, plays a key role in angiogenesis. Barley‐derived (1.3) β‐d‐glucan (β‐d‐glucan) is a natural water‐soluble polysaccharide with antioxidant properties. To explore the effects of β‐d‐glucan on MnSOD‐related angiogenesis under oxidative stress, we tested epigenetic mechanisms underlying modulation of MnSOD level in human umbilical vein endothelial cells (HUVECs) and angiogenesis in vitro and in vivo. Long‐term treatment of HUVECs with 3% w/v β‐d‐glucan significantly increased the level of MnSOD by 200% ± 2% compared to control and by 50% ± 4% compared to untreated H2O2‐stressed cells. β‐d‐glucan‐treated HUVECs displayed greater angiogenic ability. In vivo, 24 hrs‐treatment with 3% w/v β‐d‐glucan rescued vasculogenesis in Tg (kdrl: EGFP) s843Tg zebrafish embryos exposed to oxidative microenvironment. HUVECs overexpressing MnSOD demonstrated an increased activity of endothelial nitric oxide synthase (eNOS), reduced load of superoxide anion (O2−) and an increased survival under oxidative stress. In addition, β‐d‐glucan prevented the rise of hypoxia inducible factor (HIF)1‐α under oxidative stress. The level of histone H4 acetylation was significantly increased by β‐d‐glucan. Increasing histone acetylation by sodium butyrate, an inhibitor of class I histone deacetylases (HDACs I), did not activate MnSOD‐related angiogenesis and did not impair β‐d‐glucan effects. In conclusion, 3% w/v β‐d‐glucan activates endothelial expression of MnSOD independent of histone acetylation level, thereby leading to adequate removal of O2−, cell survival and angiogenic response to oxidative stress. The identification of dietary β‐d‐glucan as activator of MnSOD‐related angiogenesis might lead to the development of nutritional approaches for the prevention of ischemic remodelling and heart failure.